Estuaries Hidrofisis Characteristic - Maxi Tendean (Indonesian Journal of Environment and Sustainable Development, 2017)
Estuaries hidrofisis characteristic can be based on the moon changes phases as the earth's major satellite, distribution of physical variable position, flow rate, bed material transport, and weather condition in Indonesia (dry and wet season). Physical characteristic of flow rate and the change of bed material transport sliding as bed load along the estuaries is spatially functioned by an expert to study water flow characteristic. Analysis of velocity pattern as well as the moon phases and seasons becomes the determiner of spreading pattern of bed load that is important to perform later. Analysis of flow rate variable and bed load is especially based on the phases of the moon and seasons. Their change along the river estuary can show the characteristic of erosion change and sediment deposition in the estuary. Measurement in the rainy season was done during full moon and first quarter moon, as well as in the dry season of full moon when sea level rises and downs. Identification of estuaries flow shows six measurement segments and seventeen measurement positions which becomes the basic analysis of hidrofisis variable change along the estuaries. The measured variable during high tide includes water flow around the riverbed surface, bed load concentration, material diameter of riverbed, water flow of river bed surface during high tide, and bed load concentration. Analysis of hidrofisis characteristic of estuaries will refer to two things, firstly, profile of water flow parameter and load change of basic material. Secondly, modeling and data interpolation stated in absolute mean deviation and bias in data of modeling result as well as interpolation towards data of measurement result. Water flow characteristic during low tide in rainy season of full moon shows higher price compared to the first quarter of rainy season. It becomes different in the rainy season of full moon and is much lower with the decrease of gradient, that happens during high tide. While estuary hidrofisis characteristic, bed material transport of dry season during high tide of full moon is larger than rainy season during high tide of full moon and first quarter moon. Water discharge improvement is always accompanied by flow rate increase (in the rainy season). During wet season, change of bed material transport is much more than dry season. Bed material transport curves sand in the Ranoyapo estuary is slightly small to be  transported by flow velocity. It causes considerable high conveyance of bed material transport, even bed material load is not settled on river estuary but continued by stream into beach. Dry season of full moon with lower flow velocity compared to the rainy season of full moon and first quarter phase is evidently enough to settle bed material transport along the river estuary.  Key Words: Bed Material Transport, Estuaries ups and downs, Moon Phases, Stream